EKSPLORASI BATIK KONTEMPORER DENGAN TEKNIK PENDULUM PADA BUSANA CASUAL WANITA - Rizqiah Nurida Aini; Urip Wahyuningsih (Universitas Negeri Surabaya, 2026)
Batik has undergone a shift and transformation from its traditional values that influence various designs, media, and functions, resulting in the emergence of contemporary batik. The research aims to explore the creation of contemporary batik motifs with the pendulum technique and its application to women’s casual wear. The pendulum technique is an innovate motif making technique by ultilizing the force of gravity using a pendulum swinging with hot wax to produce a unique spiral pattern. The method in this research uses the Double Diamond Model which consist of four stages: Discover, exploring ideas, the pendulum movement is interpreted as a representation of the galaxy; Define, compiling a moodboard; Develop, creating basic design and their development and exploring pendulum technique motifs until the product is made into a garment; Deliver, the final stage where input from experts is collected. This reserch produces women’s casual wear with the application of contemporary batik using the pendulum technique. Responses from fashion experts regarding clothing realized with the application of the pendulum technique are classified as very good. Aspects assessed include creativity and originality, color and visuals, motif composition, and functionality. This researh shows that batik is not only traditional cultural heritage but also a creative medium in the world of contemporary fashion.